Transitional lumbosacral vertebrae and low back pain: diagnostic pitfalls and management of Bertolotti's syndrome Dor lombar associada à vértebra de transição lombossacra: dificuldades no diagnóstico e manejo da síndrome de Bertolotti - Daniel Benzecry de Almeida; Tobias Alécio Mattei; Marília Grando Sória; Mirto Nelso Prandini; André Giacomelli Leal; Jerônimo Buzzeti Milano; Ricardo Ramina (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Bertolotti's syndrome is a spine disorder characterized by the occurrence of a congenital lumbar transverse mega-apophysis in a transitional vertebral body that usually articulates with the sacrum or the iliac bone. It has been considered a possible cause of low back pain. METHOD: We analyzed the cases of Bertolotti's syndrome that failed clinical treatment and reviewed the literature concerning this subject. RESULTS: Five patients in our series had severe low back pain due to the neo-articulation and two of them were successfully submitted to surgical resection of the transverse mega-apophysis. Taking into account the clinical and surgical experience acquired with these cases, we propose a diagnostic-therapeutic algorithm. CONCLUSION: There is still no consensus about the most appropriate therapy for Bertolotti's syndrome. In patients in whom the mega-apophysis itself may be the source of back pain, surgical resection may be a safe and effective procedure. OBJETIVO: A síndrome de Bertolotti é uma desordem congênita da coluna vertebral caracterizada pela ocorrência de uma mega-apófise transversa lombar em uma vértebra de aspecto transicional, que geralmente se articula com o sacro ou com o osso ilíaco. Tal síndrome tem sido considerada possível causa de dor lombar. MÉTODO: Análise dos casos de síndrome de Bertolotti que apresentavam dor lombar sem melhora com tratamento conservador e revisão dos artigos publicados. RESULTADOS: Foram revisados cinco pacientes que não apresentaram melhora com o tratamento clínico, sendo que dois foram submetidos à ressecção cirúrgica da mega-apófise transversa. Considerando a experiência adquirida com estes casos, os autores propõem um algoritmo para diagnóstico e tratamento da Síndrome de Bertolotti. CONCLUSÃO: Ainda não há consenso sobre qual é a terapia mais apropriada para a Síndrome de Bertolotti. Em pacientes em que a mega-apófise parece ser a origem da lombalgia, a ressecção cirúrgica parece ser um procedimento seguro e efetivo.